PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN MATERI STATISTIKA DI KELAS VIII SMP NEGERI 10 MANADO - Mandagi, Rinai Zita; Mangobi, James U.L; Kaunang, Derel F (JURNAL LEMMA, 2025)
This study was motivated by the low student learning achievement in Statistics material and the lack of active involvement of students in learning, so it aims to test the effectiveness of the Problem Based Learning (PBL) model in improving learning outcomes compared to the Direct Instruction (DI) model. Using quasi-experiment method with Posttest Only Control Group Design, the research involved class VIII-3 as the experimental group (PBL) and VIII-5 as the control group (DI). The analysis results showed that the average posttest score of the PBL group was significantly higher than the DI group, proving that the application of PBL can improve students' understanding of Statistics material at SMP Negeri 10 Manado. This finding recommends the use of PBL as a learning alternative while opening up opportunities for further research with supporting variables such as the role of the teacher or learning media.